ELABORAÇÃO DE APLICATIVO DE AVALIAÇÃO NUTRICIONAL PARA TELEFONES CELULARES COM SISTEMA ANDROID - Daniele Lima Cruz; Márcia Nacif (Universidade do Estado do Rio de Janeiro, 2015)
New nutritional guidance tools have been used by varioushealth professionals. Among these are health-oriented cellphone applications with several resources that can help theuser maintain a healthy diet. In this context, this study had asmain objective to build a nutritional assessment application formobile phones with Android system. An app called Diet Help wasdeveloped, with seven screens: "User Profile", "Food Record","Summary of the day", "Diet history", "Food calories", "HealthyEating" and "Delete User". The main programming languagesused were Android Java, Javascript and SQlite for database. DietHelp allows calculation of body mass index, nutritional statusaccording to age and sex, informs recommended daily energyintake, the amount of calories and nutrients consumed in eachmeal and if consumption (ou intake) is in accordance with therecommended levels for the user age and sex. It also allowsusers to find the amount of calories and nutrients per 100g ofany food and provides information on healthy eating based onthe Food Guide for the Brazilian Population [Guia Alimentar para aPopulação Brasileira]. DOI: 10.12957/demetra.2015.15555